Comparative sensitivity analysis between two methods for species differentiation and interspecies cross contamination in animal cell culture - Mohammadi, Ashraf; Farzinpoor, Mansooreh; Lotfi, Mohsen; Ghorbani, Raiehaneh (Archives of Medical Laboratory Sciences, 2019)
Background: The present article focuses on the design and development of a highly sensitive and convenient approach for rapid detection of animal species and cross contaminations quickly during cell cultures as most important document for manufacturing working cell bank system. This test is one of the four most important documents during implementing the banking system. By using this modified test, one of the major risks in cell culture laboratories, cross- contamination and misidentifications with microorganisms of cell lines will also be important to be confirmed. Materials and Methods: A PCR _RFLP assay was optimized based on the use of a pair of primers that anneal to a portion the cytochrome b gene in all the species. The amplification product was digested with a panel of six restriction enzymes and the pattern derived was resolved on 3% high resolution agarose gel for 2 species, human & primate. As a control test iso enzyme assay as a conventional method was used. Results: This protocol produced a unique restriction pattern and the origin was confirmed by this analysis. The sensitivity in detecting interspecies cross contamination was at least 100 pg DNA/reaction, which was sufficient for detection of each species of DNA. Conclusion: The method developed in this study will provide a useful tool for the authentication of animal species and is also more comparable and time consuming, compared with conventional analysis. Using this method, significant differences between human and non-human as well as cross- contamination between different cell lines are simply distinguished.